Use of Camellia sinensis in green synthesis of pure and nickel-doped copper oxide nanoparticles and investigation of their photocatalytic degradation and antibacterial effects - Nikhil Parasar; Bidhan Mohanta; Sandeep Das; Manoj Bora; Piyush Pandey (Nano Express)
Green synthesis of metal and metal oxide nanoparticles has been widely studied recently. The cost-effectiveness, as well as the environment-friendly green approach to synthesizing nanoparticles, is a true achievement for the scientific community. In this study, tea (camellia sinensis) leaf extract was used to synthesize pure copper oxide nanoparticles (CuO NPs) and nickel doped copper oxide nanoparticles (Ni/CuO NPs). Synthesized nanoparticles were characterized with UV-visible spectroscopy, PL spectroscopy, PXRD, and FESEM. The optical study of the sample revealed a narrow band gap of 1.60 eV in CuO NPs and 1.98 eV in Ni/CuO NPs. The incorporation of nickel into copper oxide has increased its band gap significantly. FESEM images show a clear picture of spherical shaped CuO and Ni/CuO NPs. PXRD shows that both samples have fine crystalline structure. The photocatalytic degradation effects were tested using methylene blue (MB) dye in the presence of sunlight. Moreover, the antibacterial activities of the samples showed remarkable results against Gram-positive Staphylococcus aureus ( S. aureus ) bacteria. It is found that the nickel-doped CuO NPs are more effective in photocatalytic degradation and antibacterial activities than pure CuO NPs.